Functional shikimate dehydrogenase from Mycobacterium tuberculosis H37Rv: Purification and characterization - Fonseca, I. O.; Magalhaes, MLB; Oliveira, J. S.; Silva, R. G.; Mendes, M. A.; Palma, Mario Sergio [UNESP]; Santos, D. S.; Basso, L. A. (Elsevier B.V., 2006)
Tuberculosis (TB) poses a major worldwide public health problem. The increasing prevalence of TB, the emergence of multi-drug-resistant strains of Mycobacterium tuberculosis, the causative agent of TB, and the devastating effect of co-infection with HIV have highlighted the urgent need for the development of new antimycobacterial agents. Analysis of the complete genome sequence of M. tuberculosis shows the presence of genes involved in the aromatic amino acid biosynthetic pathway. Experimental evidence that this pathway is essential for M. tuberculosis has been reported. The genes and pathways that are essential for the growth of the microorganisms make them attractive drug targets since inhibiting their function may kill the bacilli. We have previously cloned and expressed in the soluble form the fourth shikimate pathway enzyme of the M. tuberculosis, the aroE-encoded shikimate dehydrogenase (mtSD). Here, we present the purification of active recombinant aroE-encoded M. tuberculosis shikimate dehydrogenase (mtSD) to homogeneity, N-terminal sequencing, mass spectrometry, assessment of the oligomeric state by gel filtration chromatography, determination of apparent steady-state kinetic parameters for both the forward and reverse directions, apparent equilibrium constant, thermal stability, and energy of activation for the enzyme-catalyzed chemical reaction. These results pave the way for structural and kinetic studies, which should aid in the rational design of mtSD inhibitors to be tested as antimycobacterial agents. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Mycobacterium tuberculosis; shikimate pathway; shikimate dehydrogenase; aroE; enzyme kinetics; protein purification; drug target